Modifications of Semantic Space of Interpersonal Perception of Bilingualism at Different Levels of Discursive Abilities - Anatoly N Voronin (Peoples' Friendship University of Russia (RUDN University), 2018)
The article is devoted to psychosemantic research of interpersonal perception of bilinguals by people with different level of discursive abilities. The construct "discursive abilities" was introduced in the study of the formation of artificial bilingualism. Discursive abilities allow a person to effectively initiate, support, deploy and complete the communication process. The influence of discursive abilities on the structure of the semantic space has not previously been explored. The purpose of this study was to elucidate the modification of the semantic space of interpersonal perception of bilinguals and its dependence on the level of development of discursive abilities. The reconstruction of the semantic space of interpersonal perception of bilinguals on the two contrasting samples showed that the dimension and content of the semantic spaces of people with high and low level of discursive abilities are significantly different. For the sample with a high level of discursive abilities, four significant factors of semantic space were identified: enthusiasm, sympathy, friendliness, caution. The semantic sample space with a low level of discursive abilities turned out to be three-dimensional: enthusiasm, sympathy, openness to experience. To compare both spaces, the "pooled data method" was used. This allowed us to identify two areas of significant differences in the interpersonal perception of bilinguals in people with a low and high level of discursive abilities: the higher the level of discursive abilities, the more people tend to perceive bilinguals as more active and open in communication.